The Impact of Migration and Remittance on the Economic Development of a Country : A Case Study on Nepal - J.B. Rana, Trishakti (2014)
Remittances occupy an important place at the intersection of migration with finance and development. Migration and remittance are generally perceived as risk-spreading and coinsurance livelihood strategies pursued by households and families. They have the potential to improve well-being, stimulate economic growth and reduce poverty directly and indirectly. Remittances are one of the key benefits that migration brings to originating countries. Migrant workers’ remittances have now become an important source of foreign capital for developing countries. With the fall of foreign direct investment and capital market flows due to recession in high-income countries, inflow of remittance has single handedly supported the economy of developing countries. Evidence shows that a significant amount of remittance transfers to developing countries are spent on household consumption. Remittance flows worldwide are projected to reach USD 515 billion by the year 2015. The history of Nepali citizens going overseas to seek employment dates back to the early 19th century when the British army began to recruit Gurkhas into their armed forces. Over the years, both migration and remittance have contributed significantly towards the development of the Nepalese economy. Remittance alone contributed 22 percent of the total GDP for the year 2012. These significant features and contribution of migration and remittance have led to this research’s main objective of analyzing the impact of migration and remittance on the economic development of Nepal.